(untitled) (Informatica, 2017)
This paper describes a micro-simulation model which combined car following with lane change model. For that, we proposed a new car-following model which is an extended of velocity-separation difference model (VSDM) by introducing a new optimal velocity function, named a modified velocity-separation difference model (MVSDM) which react better in braking case. The problems of collision in urgent braking case existing in the previous models were solved. Furthermore, the simulation results show that (MVSDM) can exactly describe the driver’s behavior under braking case, where no collision occurs.